Exchange Competition, Entry, and Welfare - Giovanni Cespa; Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2018)
We assess the consequences for market quality and welfare of different entry regimes and exchange pricing policies in a context of limited market participation. To this end we integrate a two-period market microstructure model with an exchange competition model with entry in which exchanges supply technological services, and have market power. We find that technological services can be strategic substitutes or complements in platform competition. Free entry of platforms delivers a superior outcome in terms of liquidity and (generally) welfare compared to the case of an unregulated monopoly. Controlling entry or, even better typically, platform fees may further increase welfare. The market may deliver excessive or insufficient entry. However, if the regulator is constrained to not making transfers to platforms then there is never insufficient entry.
Keywords: G10; G12; G14; 330; market fragmentation; welfare; endogenous market structure; platform competition; Cournot with free entry; industrial organization of exchanges